2016
DOI: 10.1111/head.12871
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Depression on Health and Medical Care Utilization and Expenses in US Adults With Migraine: A Retrospective Cross Sectional Study

Abstract: Comorbid depression in subjects with migraine was associated with higher total and migraine-related health expenses and increased likelihood of all-cause ED visits. Comorbid depression management might be incorporated into migraine intervention program to improve treatment outcomes and produce potential cost savings. Further studies are needed to assess long-term effects of depression on migraine progression and health care utilization patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…These observed cost differences appear to reflect both the increased disease severity and the increased rates of comorbidities in chronic migraine compared with episodic migraine . For example, depression increased the likelihood of all‐cause emergency department visits, and was associated with higher total and migraine‐related health expenses …”
Section: Burden Of Diseasementioning
confidence: 99%
“…These observed cost differences appear to reflect both the increased disease severity and the increased rates of comorbidities in chronic migraine compared with episodic migraine . For example, depression increased the likelihood of all‐cause emergency department visits, and was associated with higher total and migraine‐related health expenses …”
Section: Burden Of Diseasementioning
confidence: 99%
“…Seven studies gave data for the disability outcome for adults with migraine and comorbid depression and/or anxiety ( Table 3). The results from the studies included in this review showed that depression and anxiety had a negative impact on the disability depression compared to those without depression (OR=1.36, 95% CI: 1.08, 1.71) [29]. This study suggests that depression increases healthcare utilization among adults with migraine, however, the impact of anxiety alone or comorbid depression and anxiety on healthcare utilization not been evaluated yet.…”
Section: Humanistic Burden Of Comorbid Depression and Anxiety Among Amentioning
confidence: 71%
“…These studies found that that direct medical care costs were higher for those with depression and/or anxiety. In terms of healthcare utilization, only one study identified in this review was used a large national U.S. data, this study have reported that adults with migraine and depression have a significantly higher hospitalizations ( [29]. The higher healthcare utilization could be due to that depression may exacerbate migraine symptoms and increase the need for healthcare utilization and migraine treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations